The Effectiveness of Kopiko Sugar Free Advertisement in Korean Drama My Demon in East Java Society - Tania Devina; Astri Yogatama; Felicia Goenawan (Journal of Content and Engagement, 2024)
In December 2023, Kopiko appeared with a new variant, namely sugar free and did product placement in the drama My Demon. The purpose of this study is to determine the effectiveness of Kopiko Sugar Free product placement advertising in Korean drama My Demon on East Java. In this study, the effectiveness will be measured by customer response index, which uses the indicator stages of awareness, comprehend, interest, intention and action. This research approach is quantitative descriptive. The technique used is non-probability sampling and purposive sampling with a sample size of 100 respondents. The result of this research is that the Kopiko Sugar free product placement advertisement is in the effective stage as evidenced by the final result of the CRI multiplication of 58%. This is due to the utilization of the three dimensions of product placement done simultaneously, namely visual, audio and plot connection dimention